Lessons on social inclusion for transformative forest-based bioeconomy solutions - Sarmiento Barletti, J.P.; Monterroso, I.; Atmadja, S. (Center for International Forestry Research, 2021)
The transformational potential of bioeconomy solutions to advance environmental sustainability rests on whether they can deploy strategies for social sustainability. Bioeconomy can learn important lessons on social inclusion from previous research on redistribution, recognition, and representation concerns in forest-based climate initiatives. Initiatives should recognize Indigenous Peoples and local communities as right-holders in their design and implementation. They should ensure that enabling conditions are in place for women, youth and Indigenous Peoples and local communities to participate effectively throughout an initiative’s lifetime. Initiatives should also provide mechanisms to promote a just and fair distribution of costs and benefits between stakeholders.